Diseases in Chronic Non-infective Diarrhea - Marcellus Simadibrata; Aziz Rani; Daldiyono Daldiyono; Ari Fahrial Syam; GNJ Tytgat; Vera Yuwono; L A Lesmana; Iwan Ariawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2004)
Background: Chronic diarrhea is common in Indonesia. The chronic non-infective diarrhea cases seem to be increasing recently. The aim of this study is to reveal the pattern of diseases that can cause chronic non-infective diarrhea. Methods: We examined all patients suffering from chronic non-infective diarrhea over a six years period. The patients underwent physical examination and performed laboratory tests, colon enema X-ray, colonoscopy, ileoscopy, upper gastrointestnal endoscopy and small bowel X-ray. Result: Chronic non-infective diarrhea was observed in 107 (51.7%) cases from 207 chronic diarrhea cases respectively. The frequently found abnormalities that had caused chronic non-infective diarrhea were carbohydrate maldigestion (62.61%), colorectal cancer (14.01%), Crohn’s disease (11.21%), ulcerative colitis (9.34%), irritable bowel syndrome (8.41%), colorectal polyp (8.41%) etc. Conclusion: The most frequent abnormality found in chronic non-infective diarrhea was maldigestion.   Keywords: Chronic diarrhea, non-infective